UPAYA MENINGKATKAN KEMANDIRIAN ANAK MELALUI POLA ASUH DEMOKRATIS - Roudlotun Ni'mah; Zahrotun Nikmah (Atthiflah: Journal of Early Childhood Islamic Education, 2020)
Independence is very important in a person's life, because with independence children can become more responsible in meeting their needs and fostering confidence in children. A child who has a sense of independence will be able to adjust to the environment and the circumstances of the child's own environment and be able to overcome the difficulties that occur. Children's independence is communicative during development, where individuals will continue to learn to be independent in facing environmental situations, so as to be able to think and act alone with their independence. This type of research is qualitative research, which is research in the form of words, not in the form of numbers. Qualitative research is obtained through a wide variety of data collection techniques such as interviews, document analysis, focused discussions, or observations that have been outlined in field records (transkip). Another form of research cauldron This research was conducted at the SDN TAPELAN Institution precisely located in Tapelan Village, Bojonegoro Regency Cotton District. The results of this study, that efforts of independence by democratic parenting methods accustom children to eat alone, by means of democratic parenting tells children to eat patiently. Democratic parenting sets an example and tells children to wear their own clothes in a democratic parenting way. Democratic parenting the way parents provide motivation or encouragement to children that children are able to do things independently by means of democratic parenting